Edmund Pevensie’s Violation of Pawongan Values in The Lion, the Witch, and the Wardrobe by C.S. Lewis - Ni Kadek Anggi Cahya Susaniari; Ni Komang Arie Suwastini; I Nyoman Pasek Hadi Saputra; Zhu Minxia; Ni Nyoman Artini (English Education Department STKIP Agama Hindu Singaraja, 2026)
Pawongan in Tri Hita Karana is a universal value that functions as a foundation for character education, particularly in shaping children to behave ethically and develop social awareness. Introducing positive values through Pawongan-based character education is not enough, because children also need to be introduced to actions that violate Pawongan values, so that they know which actions are wrong and as guidance for not doing those actions. This study aims to introduce these violating actions through an analysis of Edmund Pevensie's characterization in The Lion, the Witch, and the Wardrobe novel by C.S. Lewis that violates Pawongan values. This study used an interactive qualitative data analysis model by Miles, Huberman, and Saldana (2014), which includes data collection, data condensation, data display, and conclusion drawing and verification. The results of the study showed that Edmund Pevensie violates Pawongan values through selfish, betrayal, bullying, and dishonesty actions towards his siblings, which have an impact on damaged social relationships and decreased trust given by his siblings. This research is expected to enrich local wisdom-based character education in children's literature and encourage future research to explore further world literary works that contain local values.